Policies and Power Plays: Political Elites, Institutional Change, and the Hanseatic Kontor in Fifteenth-century Deventer. - Klinkhamer, Reinder (TSEG - The Low Countries Journal of Social and Economic History, 2025)
Since the work of Oscar Gelderblom, city governments are increasingly acknowledged for their role in shaping economic institutions. This article aims to understand what informed their economic policies. It focuses on the fifteenth-century Deventer city government and its response to the relocation of the Hanse’s permanent trading post (the kontor) from Bruges to Deventer in 1451/1452. By analyzing the government’s economic policies in their economic and political context, I argue that they primarily reflect the local balance of power among different interest groups. All in all, when deciding on their economic policies, the government’s major concern was to serve the economic interests of groups whose support it needed for remaining in power.